Analisis Rekrutment dan Seleksi Karyawan PT Asuransi Jiwa Syariah Bumiputera Cabang Jambi - Mustika Mustika; Ade Irma Suryani (Universitas Batanghari Jambi, 2022)
PT. Asuransi Jiwa Syariah Bumiputera in conducting employee recruitment is fully carried out by the head office or regional office, while agent recruitment is carried out by branch offices using two internal methods and external methods. Second, the selection process carried out at PT. Asuransi Jiwa Syariah Bumiputera Jambi Branch is in line with recruitment, during the internal recruitment process the selection process is carried out internally and does not go through many series of selections, while during the external recruitment process the selection stages are carried out gradually starting from from administrative tests, interviews, academic tests, written tests and to the final interview that determines whether the application is accepted or not. Third, the factors that become the internal strength of the recruitment and selection of PT Asuransi Jiwa Syariah Bumiputera Jambi Branch are using different procedures between internal recruitment and external recruitment, optimizing existing resources, and having a conducive work environment. While the factor that becomes a weakness in the recruitment of PT Asuransi Jiwa Syariah Bumiputera Jambi Branch is when internal recruitment is used, it means that there will be employee transfers between units which will cause problems if there is no replacement, while using external recruitment procedures and costs are not small. Fourth, external factors that become opportunities for recruitment and selection of PT Asuransi Jiwa Syariah Bumiputera, namely the opening of opportunities for contract employees and non-permanent employees to become permanent employees of PT Asuransi Jiwa Syariah Bumiputera, opening opportunities for the general public to have a career at PT Asuransi Jiwa Syariah Bumiputera, and opening up opportunities for old employees to develop games. While the factors that pose a threat are prospective employees who are not in accordance with the company's needs, in addition to employee recruitment and marketing personnel can cause internal piracy, and promotions cause disharmony and competition between employees.